Myo-inositol as a carbon source in Chlorella sp. production - Erbil, Gokhun Cagatay; Elp, Mahmut; Durmaz, Yasar (Elsevier BV, 2024)
The study aimed to investigate the possible use of myo-inositol as a carbon source in Chlorella sp. culture. Firstly, experiments were conducted with different myo-inositol concentrations and glycerol in flasks. Secondly, a laboratory-scale tubular photobioreactor (PBR) was operated with CO2 and myo-inositol to determine performance under industrial production conditions. The highest dry weight of the experiments with flasks was 1.62 +/- 0.02 g.L-1 and was obtained with 1 g.L-1 myo-inositol concentration. Myo-inositol yielded two times higher lipid accumulation compared to glycerol in the experiment with flasks and 12 % compared to CO2 in the PBR experiment. The results revealed that myo-inositol is one of the most efficient carbon sources with 0.86 CBCR (carbon to biomass conversion rate). Even if myo-inositol is more expensive than many carbon sources such as CO2, high efficiency and less light energy expenses make it a competitive carbon source in Chlorella sp. production.

This article is based on the PhD thesis study (807027) of Go d khun Cag atay ERBI L conducted at Kastamonu University Institute of Natural Sciences, Kastamonu, Turkey.
Keywords: Pigment; Mixotrophic; Microalgae; Myo-Inositol; Lipid; Fatty Acid